A minting mold for the eFranc: A policy paper - Hans Gersbach; Roger Wattenhofer (ETH Zurich, CER-ETH - Center of Economic Research, 2020)
We suggest a blueprint for an eFranc as a possible complement for the Swiss monetary system to ensure the long-term stability of its money. An eFranc is a non-interest-bearing digital form of the legal tender available to the public. The public can convert banknotes or part of its bank deposits into eFrancs, subject to the banks' ability to obtain the corresponding amount of eFrancs from the central bank. There is free conversion of eFrancs into bank deposits (and into banknotes). For the technical implementation of the eFranc, we suggest a two-layer system combining a permissioned asynchronous blockchain without consensus which provides a secure environment for validating transactions (base layer) plus a peer-to-peer payment network (top layer).
Keywords: 330; eFranc; Swiss Monetary System; Financial Stability; Swiss NationalBank; Proof-of-stake Blockchains